Irradiación de especias producidas en la Argentina - Kairiyama, E.; Narvaiz, Patricia; Lescano, Graciela; Kaupert, Norma Lucía (Publitec S.A.E.C. y M.; Argentina, 1988)
Fil: Kairiyama, E. Comisión Nacional de Energía Atómica; Argentina